IMPACT OF PARAMETERS α, β AND ρ ON QUALITY OF SOLUTION TO TRAVELLING SALESMAN PROBLEM BY ANT COLONY OPTIMIZATION ALGORITHM - Míča, Ondřej (Sciemcee Publishing, 2018)
The travelling salesman problem is a well-known and popular optimization problem. Because it is an NP-hard problem, the number of permissible solutions is very high – it grows with the number of nodes in the transport network. So even with nowadays computers, it takes very large amount of time to solve TSP with exact methods. Ant colony optimization is metaheuristic algorithm inspired by nature. It has several parameters, which have to be set before the first run of algorithm and their correct setting is important for finding a satisficing solution. This paper deals with the effect of setting these parameters on the quality of the solution found.
Vliv nastavení parametrů α, β a ρ na výsledné řešení úlohy obchodního cestujícího metodou mravenčí kolonie
Keywords: ant colony optimization; metaheuristic; optimization; travelling salesman problem; metoda mravenčí kolonie; metaheuristické metody; optimalizace; úloha obchodního cestujícího